PENAMPILAN REPRODUKSI SAPI POTONG LOKAL DI KECAMATAN BOLAANG KABUPATEN BOLAANG MONGONDOW - Boda, Brenda; Lomboan, A.; Paath, J.F.; Hendrik, M. J. (Universitas Sam Ratulangi, 2020)
REPRODUCTIVE PERFORMANCE OF LOCAL BEEF COWS IN BOLAANG DISTRICT OF BOLAANG MONGONDOW REGENCY. This study aims to determine the reproductive performance of local beef cattle in Bolaang District, BolaangMongondow Regency. This study used local beef cattle owned by breeders who were taken as samples in several villages in Bolaang District, Bolaang Mongondow Regency. This study used a survey method to obtain primary and secondary data collection. Data analysis regarding the studied variables used descriptive analysis referring to the measurement of each variable. The results showed that service per conception was 1.38, conception rate was 70%, pregnancy period was 276.47 days, animal age of first calving was 32.022 months, and calving interval was 375.26 days. Based on these results of study, it can be concluded that the reproductive performance of local beef cattle in Bolaang district, Bolaang Mongondow regency was categorized into normal reproductive performance of local beef cattle.Â Key word: Reproduction, Local beef cow, Bolaang district,Â Â